Population dynamics of jerbung shrimp (Penaeus merguensis) in Samboja Kuala Waters, Kutai Kartanegara Regency - Nilam Cahya; Muhammad Syahrir Ramang; Abdunnur Abdunnur (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Jerbung shrimp (Penaeus merguensis) is one of the species caught in the waters of Samboja Kuala. In an effort to conserve and utilize as well as high fishing intensity, the possibility of exploiting shrimp resources will be threatened. This research was conducted in November-December 2022. This study aims to examine sex ratios, age groups, growth rates, mortality and exploitation, growth pattern, and yield per recruitment. Jerbung shrimp (P.merguensis) in Samboja Kuala waters, Kutai Kartanegara. Shrimp sampling using a mini trawl operated in the waters of Samboja Kuala, Kutai Kartanegara. The sex ratio of jerbung shrimp was 1:1.29. The coefficient of growth rate (K) is 0,770 and the estimated length in nature (L∞) is 187,33. Jerbung shrimp with a natural mortality value (M) = 0,197/year, a mortality value due to fishing (F) = 0,143, and a total mortality value (Z) = 1,061, with an exploitation value (E) = 0,135 which means that it is still at level it should be. The peak of new additions to females occurred in July as much as 18,56%. The Y/R capability was 0,071/year, and Emax calculated the Y/R relationship with the exploitation rate, which was 0,42.